The wisdom of distinguishing between male and female inheritance according to some provisions in Sharia and law (Islamic Sciences Journal, 2024)
ABSTRACTThis study discusses the wisdom of distinguishing between males and females in inheritance for some provisions in Sharia and law and according to circumstances, and the legal basis for female inheritance in the Qur’an, Sunnah and consensus, as well as the basis of legislation through legal texts related to the interests of males and females for inheritance according to different circumstances: there are cases in which the female inherits half of the male. That is, the multiplication of the male over the female, which is the essence of justice and wisdom, and in cases where women inherit like men, that is, equality in inheritance between male and female. If a woman inherits more than a man, the woman inherits and the man does not. As an expression of the importance of legal texts. Explaining its significance to give a clear vision of the problematic issue in order to achieve an accurate understanding of a system of legal and legal rulings related to inheritance, and doubts raised about the female share of inheritance, and to refute these doubts and respond to them with evidence. The Iraqi legislator has adopted the provisions of the Personal Status Law in the Inheritance Law. He came up with a special legal system to give rights to their owners in light of divine legislation through legal texts related to inheritance provisions.
Keywords: Wisdom, discrimination, inheritance, rulings, Sharia, law.